Homodimerization regulates an endothelial specific signature of the SOX18 transcription factor. Issue 21 (18th October 2018) - Moustaqil, Mehdi; Fontaine, Frank; Overman, Jeroen; McCann, Alex; Bailey, Timothy L; Rudolffi Soto, Paulina; Bhumkar, Akshay; Giles, Nichole; Hunter, Dominic J B; Gambin, Yann; Francois, Mathias; Sierecki, Emma
Abstract: During embryogenesis, vascular development relies on a handful of transcription factors that instruct cell fate in a distinct sub-population of the endothelium (1 ). The SOXF proteins that comprise SOX7, 17 and 18, are molecular switches modulating arterio-venous and lymphatic endothelial differentiation (2, 3 ). Here, we show that, in the SOX-F family, only SOX18 has the ability to switch between a monomeric and a dimeric form. We characterized the SOX18 dimer in binding assays in vitro, and using a split-GFP reporter assay in a zebrafish model system in vivo . We show that SOX18 dimerization is driven by a novel motif located in the vicinity of the C-terminus of the DNA binding region. Insertion of this motif in a SOX7 monomer forced its assembly into a dimer. Genome-wide analysis of SOX18 binding locations on the chromatin revealed enrichment for a SOX dimer binding motif, correlating with genes with a strong endothelial signature. Using a SOX18 small molecule inhibitor that disrupts dimerization, we revealed that dimerization is important for transcription. Overall, we show that dimerization is a specific feature of SOX18 that enables the recruitment of key endothelial transcription factors, and refines the selectivity of the binding to discrete genomic locations assigned to endothelial specific genes.